2014
DOI: 10.1155/2014/270676
|View full text |Cite
|
Sign up to set email alerts
|

Change of Muscle Architecture following Body Weight Support Treadmill Training for Persons after Subacute Stroke: Evidence from Ultrasonography

Abstract: Although the body weight support treadmill training (BWSTT) in rehabilitation therapy has been appreciated for a long time, the biomechanical effects of this training on muscular system remain unclear. Ultrasonography has been suggested to be a feasible method to measure muscle morphological changes after neurological diseases such as stroke, which may help to enhance the understanding of the mechanism underlying the impaired motor function. This study investigated the muscle architectural changes of tibialis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
1
40
1
Order By: Relevance
“…US images were analyzed using a custom-written MATLAB program (version: R2017b) that was, similar to previous reports 25 . The deep and superficial aponeuroses of each respective muscle were firstly identified.…”
Section: Methodsmentioning
confidence: 99%
“…US images were analyzed using a custom-written MATLAB program (version: R2017b) that was, similar to previous reports 25 . The deep and superficial aponeuroses of each respective muscle were firstly identified.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study of subacute stroke patients reported that there was a change in muscle structure after gait training on a treadmill [25]. Specifically, the results showed larger pennation angle and muscle thickness of the tibialis anterior and longer fascicle length of the medial gastrocnemius after the training.…”
Section: Discussionmentioning
confidence: 94%
“…Muscle thickness affects muscle function and further affects limb function [ 15 ]. CT and MRI have been the standard methods for accurate measurement of muscle thickness [ 6 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the validity and reliability of using MSUS to measure acromiohumeral distance (AHD) for assessing GHS [ 9 13 ]. Nozoe et al have elucidated that the recovery of limbs function can be assessed by measuring changes in the thickness of dominated muscles before and after the treatments [ 14 , 15 ]. Some researchers have confirmed the validity and accuracy of using MSUS to measure muscle thickness [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%